The influence of dorsomedial hypothalamic nucleus on contralateral paraventricular nucleus in NMDA-mediated cardiovascular responses - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLHAN, REZZAN (My University, 2003)
Dorsomedial (DMH) and paraventricular nuclei (PVN) are two important hypothalamic structures involved in the central regulation of cardiovascular regulation. L-Glutamic acid and gamma-aminobutyric acid (GABA) were demonstrated to elicit cardiovascular responses when administered via intracerebroventricular injection or parenchymal microinjections into the hypothalamic nuclei, participating in central cardiovascular regulation. In this study the interaction between the DMH and the PVN were investigated by means of microinjection and microdialysis techniques in Sprague-Dawley rats. Stereotaxic surgery was performed for the insertion of intracerebral parenchymal microinjection cannula into the right DMH and microdialysis probe into the left PVN. After a recovery period of 3 days, the iliac artery was cannulated for monitoring pulsatile blood pressure and heart rate by means of pressure transducer connected to a polygraph. Microinjection of 50 pmol NMDA into the DMH was performed and microdialysis perfusates were collected simultaneously from the PVN in the conscious rat model. L-Glutamic acid and GABA levels were analyzed by an isocratic HPLC method with the aid of a fluorescent detector. Microinjection of 50 pmol NMDA into the DMH produced significant increases in mean arterial pressure and heart rate. NMDA microinjection into the DMH produced a significant increase in L-glutamic acid release in the PVN, but no significant change in GABA release was observed. These results may indicate that stimulation of the DMH by NMDA results in subsequent stimulation of the PVN.
Keywords: Female; Animals; Male; Rats; Blood Pressure; Time Factors; Functional Laterality; Glutamic Acid; Heart Rate; Rats, Sprague-Dawley; gamma-Aminobutyric Acid; N-Methylaspartate; Microinjections; Paraventricular Hypothalamic Nucleus; Microdialysis; Dorsomedial Hypothalamic Nucleus; Excitatory Amino Acid Agonists